The Effect of Eco-Enzymes on the Growth and Productivity of Vegetable Plants : Literature Review - Aldo David Dora; R. Susanti; Talitha Widiatningrum (JST (Jurnal Sains dan Teknologi), 2026)
Eco-enzyme is an organic liquid produced by the fermentation of kitchen waste and crop residues that has great potential to address organic waste problems while increasing agricultural productivity sustainably. This innovation supports the reduction of household organic waste volume and the implementation of environmentally friendly agricultural systems. This study aims to evaluate the effect of ecoenzyme on the growth and productivity of vegetable plants. The method used in writing this literature review is a narrative review. Data search using electronic data sources, namely Garuda, Google Scholar, and Semantic Google Scholar. Then, the search found 15 articles. The results of the study indicate that the administration of ecoenzyme has a positive impact on the growth and productivity of vegetable plants. The optimal concentration of ecoenzyme was found in the range of 3% and 10 ml/L for growth, and 1.5 ml/L of water and 20 ml/L for productivity. Ecoenzyme increases soil fertility, improves soil structure, and encourages nutrient and water absorption by plant roots. In addition, the plant hormone content in ecoenzyme such as auxin, gibberellin, and cytokinin helps maximize vegetative growth, generative growth, and fruit ripening. Despite its many advantages, ecoenzymes take longer to show optimal results than inorganic fertilizers, so they are often used as a supplement in organic farming systems. To optimally meet plant nutritional needs, a combination of other organic fertilizers and good soil management practices is still necessary. Therefore, the use of ecoenzymes as a liquid organic fertilizer has been shown to improve the quality of vegetable crops, both in terms of growth, yield, and nutritional content.